Who programs the teacher? Rethinking bias and inclusion in AI-powered Indonesian classrooms - Hasanah, Uswatun; Putra, Rizal Wahid Permana; Dzulfikri, Dzulfikri; Mistar, Junaidi (Universitas Islam Malang, 2025)
Despite the growing use of artificial intelligence (AI) in education, research often emphasizes its efficiency while overlooking its ethical implications, particularly with respect to algorithmic bias and teacher agency. This study aims at examining how junior high school teachers in Lumajang Regency, East Java, Indonesia perceive the bias and inclusivity of AI systems, and their pedagogical agencies when using AI tools in Indonesian EFL classroom settings. A qualitative approach was employed, involving questionnaire responses from 20 teachers and semi-structured interviews with 12 selected participants. The data revealed that while teachers appreciate AI for streamlining lesson planning and content generation, they are also aware of the limitations in its cultural and linguistic representation in AI-generated content. Many participants actively modify AI-generated materials to reflect their students’ local contexts better. However, only a small proportion reported receiving AI training in educational settings, highlighting a significant gap in institutional support. This study is limited by its localized sample and the reliance on self-reported data, which may affect generalizability. Nonetheless, the findings underscore the need for targeted professional development that includes not only technical training but also ethical and cultural competencies. Practically, this research informs policy on teacher preparation for AI integration. Socially, it contributes to more equitable digital education practices by centering the teacher’s role in mediating AI use. Future studies should expand geographically and include student perspectives to develop a more comprehensive understanding of AI’s impact on education.